Author Correction: Reference component analysis of single-cell transcriptomes elucidates cellular heterogeneity in human colorectal tumors. (December 2018) - Li, Huipeng; Courtois, Elise; Sengupta, Debarka; Tan, Yuliana; Chen, Kok; Goh, Jolene; Kong, Say; Chua, Clarinda; Hon, Lim; Tan, Wah; Wong, Mark; Cima, Igor; et al.
In the version of the article published, the author list is not accurate. Igor Cima and Min-Han Tan should have been authors, appearing after Mark Wong in the author list, while Paul Jongjoon Choi should not have been listed as an author. Igor Cima and Min-Han Tan both have the affiliation Institute of Bioengineering and Nanotechnology, Singapore, Singapore, and their contributions should have been noted in the Author Contributions section as "I.C. preprocessed Primary Cell Atlas data with inputs from M.-H.T." The following description of the contribution of Paul Jongjoon Choi should not have appeared: "P.J.C. supported the smFISH experiments." In the 'RCA: global panel' section of the Online Methods, the following sentence should have appeared as the second sentence, "An expression atlas of human primary cells (the Primary Cell Atlas) was preprocessed similarly to in ref. 55, " with new reference 55 (Cima, I. et al. Tumor-derived circulating endothelial cell clusters in colorectal cancer.Science Transl. Med . 8, 345ra89, 2016).